Enhancing Learning Quality: The Role Of Teacher Competence In Madrasah - Naningsih, Estuti; Hidayah, Fathi; Aniati, Ana; Baharun, Hasan (Institut Agama Islam An-Nawawi Purworejo, 2024)
This study aims to analyze the role of teacher competence in improving the quality of Islamic Religious Education learning in Madrasah Ibtidaiyah in Genteng district. This research is based on the importance of teachers' competence in delivering Islamic religious teaching materials effectively and applicatively in daily life, as well as various challenges faced by teachers, including the diversity of students' social and cultural backgrounds, limited resources, and changes in social dynamics. The research method used is a qualitative approach with the type of case study, involving in-depth interviews, observations, and documentation. The results of the research show that understanding of student needs, the application of active learning approaches, character development and moral values, and continuous professional development are key factors in improving the quality of teaching. It is expected to provide an implementation model that can be adopted by other educational institutions to improve teacher competence and, in turn, the quality of learning, which has a positive impact on students' academic and moral development.